2022
DOI: 10.1097/aud.0000000000001258
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Coupling on the Hearing Outcome After Implantation of an Active Middle Ear Implant: Comparison of the Transmission Behavior in Temporal Bone Experiments With Clinical Data

Abstract: Objectives: The active middle ear implant, Vibrant Soundbridge (VSB), can be implanted with a variety of couplers. Hearing outcome after implantation has been investigated in both temporal bone (TB) experiments and patient studies, but the relationship between experimental and clinical data is still weak in the literature. Therefore, experimental data from TB experiments should be compared with patient data in a retrospective study, in which the floating mass transducer is used with couplers of the third gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Sufficient transfer of the FMT’s energy to the inner ear is a crucial factor for proper function and is referred to as “coupling-quality” [ 11 ]. While various, mainly retrospective studies that intraoperatively measure coupling-quality have been published [ 12 17 ], studies exploring the influence of different methods of FMT fixation are sparse and only available from retrospective temporal bone experiments [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sufficient transfer of the FMT’s energy to the inner ear is a crucial factor for proper function and is referred to as “coupling-quality” [ 11 ]. While various, mainly retrospective studies that intraoperatively measure coupling-quality have been published [ 12 17 ], studies exploring the influence of different methods of FMT fixation are sparse and only available from retrospective temporal bone experiments [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although no mean postoperative coupling-quality was provided, similar observations were reported by Fröhlich and colleagues, with narrow distribution of postoperative coupling- qualities between 0 and 15 dB for 18 or 23 patients in Bland–Altman plots [ 12 ]. In addition, Müller and co-authors observed stable coupling-qualities of 12.7 dB-HL approximately 6 months after RW-Vibroplasty without intraoperative ABR measurements [ 18 ]. A loss of approximately 12 dB-HL in Vibroplasty without intraoperative ABR measurement as observed in our study control group correlates with the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations